Assessing the Adsorptive and Photodegradative Efficiencies of ZSM-11 Synthesized from Rice Husk Ash - Michael Akrofi Anang; Ruphino Zugle; Baah Sefa-Ntiri (Journal of Chemistry)
Rice husk was used to synthesize zeolite (ZSM-11). FTIR and X-ray diffraction methods were used to characterize the product. The synthesized zeolite was used to treat underground water from some communities in Cape Coast considering parameters such as total dissolved solids, total hardness, conductivity, nitrate, and phosphate. The percentage reduction in PO43− was 96.1% in Ebubonko and 92.5% in Apewosika. Similarly, the NO3− levels also decreased significantly in Kwaprow. The adsorption capability was also determined by using it to remove Pb2+ and Zn2+ from laboratory prepared solutions with varying masses. The percentage reduction recorded 90.57% and 86.61% for the 1.0 g whilst the 1.5 g showed 93.26% and 89.36%, respectively. It was also realized that the adsorption process followed a pseudo-first-order rather than the pseudo-second-order process with their R2 values of 0.9929 and 0.8503 for the pseudo-first-order and 0.9662 and 0.6912 for the second-order for Pb2+ and Zn2+, respectively. The adsorption capacity also favored the Freundlich isotherm with R2 values of 0.7578 and 0.642 rather than Langmuir isotherm with R2 values of 0.1742 and 0.3856 for Pb2+ and Zn2+, respectively. The photodegradation ability of the synthesized zeolite was analyzed using rhodamine blue (RhB) and methyl orange (MO). The process was realized to favor the pseudo-second-order with R2 values of 0.9986 and 0.0007 and a constant K2 of 0.035 and 0.021 for RhB and MO, respectively, whereas the pseudo-first-order showed an R2 value of 0.9376 and 0.9757 with K1 values of 0.03 and 0.02.